Changing the Paradigm of Craniofacial Reconstruction: A Prospective Clinical Trial of Autologous Fat Transfer for Craniofacial Deformities. Issue 5 (May 2021) - Bourne, Debra A.; Bliley, Jacqueline; James, Isaac; Donnenberg, Albert D.; Donnenberg, Vera S.; Branstetter, Barton F.; Haas, Gretchen L.; Radomsky, Elizabeth; Meyer, Ernest Michael; Pfeifer, Melanie E.; Brown, Spencer A.; Marra, Kacey G.; et al.
Abstract : Objective: This study aimed to prospectively assess outcomes for surgical autologous fat transfer (AFT) applied for traumatic and postsurgical craniofacial deformities. The minimally invasive nature of AFT has potential for reduced risk and superior outcomes compared with current reconstructive options. Background: Craniofacial deformities have functional and psychosocial sequelae and can profoundly affect quality of life. Traditional reconstructive options are invasive, invasive, complex, and often lack precision in outcomes. Although AFT is safe, effective, and minimally invasive, only anecdotal evidence exists for reconstruction of craniofacial deformities. Methods: In this Institutional Review Board-approved prospective cohort study, 20 subjects underwent AFT (average volume: 23.9 ± 13.2 mL). Volume retention over time was determined using high-resolution computed tomography. Flow cytometry was used to assess cellular subpopulations and viability in the stromal vascular fraction. Quality of life assessments were performed. After the completion of 9-month follow-up, 5 subjects were enrolled for a second treatment. Results: No serious adverse events occurred. Volume retention averaged 63 ± 17% at 9 months. Three-month retention strongly predicted 9-month retention (r=0.996, P < 0.0001). There was no correlation between the total volume injected and retention. Patients undergoing a second procedure had similar volume retention as the first ( P = 0.05). Age, sex, body mass index, and stromal vascular fraction cellular composition did not impact retention. Surprisingly, former smokers had greater volume retention at 9 months compared with nonsmokers (74.4% vs 56.2%, P = 0.009). Satisfaction with physical appearance ( P = 0.002), social relationships ( P = 0.02), and social functioning quality of life ( P = 0.05) improved from baseline to 9 months. Conclusions: For craniofacial defects, AFT is less invasive and safer than traditional reconstructive options. It is effective, predictable, and reaches volume stability at 3 months. Patient-reported outcomes demonstrate a positive life-changing impact. Abstract : Supplemental Digital Content is available in the text